Heat transfers in polymer composite materials : forming processes - Boyard, Nicolas (ISTE ; John Wiley & Sons, Inc., 2016)
This book addresses general information, good practices and examples about thermo-physical properties, thermo-kinetic and thermo-mechanical couplings, instrumentation in thermal science, thermal optimization and infrared radiation.
Previously issued in print: 2015.
Keywords: Polymeric composites.; Heat -- Transmission.; elektronické knihy; electronic books